Two-Layer Fractional Frequency Reuse With Bandwidth Partitioning for 3.5 GHz 5G Urban Macrocells - Muhammad Yaser (Jurnal Teknik Elektro Indonesia, 2026)
Inter-cell interference is still a major bottleneck in 3.5 GHz 5G urban macrocells, and it hits cell-edge users the hardest, leading to low SINR and unequal user throughput. This work studies a two-layer fractional frequency reuse (FFR) scheme that divides a macrocell into inner and outer regions using a fixed threshold radius, then splits a 100 MHz carrier into two separate subbands for the two regions. Performance is evaluated through Monte Carlo simulations using a 3D UMa path-loss model, realistic macro base-station EIRP, and a first-tier interference setting, where the outer region operates with reuse-3 while the inner region uses a reduced (thinned) reuse pattern. Four bandwidth splits between inner and outer regions are tested (25/25, 30/20, 20/30, and 15/35 MHz), and the comparison focuses on total cell capacity, spectral efficiency, and Jain’s fairness index. The results show a clear trade-off: giving more bandwidth to the inner region delivers the highest throughput, with the 30/20 MHz split producing cell capacity above 310 Mbps and spectral efficiency of 6.2 bit/s/Hz, but also the lowest fairness at 0.66. Shifting bandwidth toward the outer region improves fairness, reaching 0.82 for 20/30 MHz and 0.86 for 15/35 MHz, but reduces capacity to 260 Mbps and 234 Mbps and spectral efficiency to 5.2 bit/s/Hz and 4.7 bit/s/Hz. Overall, the study highlights how bandwidth partitioning should be chosen based on whether the priority is maximizing total throughput or improving fairness for cell-edge users.